Pemberdayaan Ibu Sebagai Strategi Pencegahan Stunting Melalui Penyuluhan dan Pelatihan Pembuatan Makanan Tambahan Bergizi Bagi Balita di Desa Girirejo - Agnes Zerlinda Bella Nathania; Pranatali Natasya Kristian; Ammar Zaky Munawar; Naufal Daffa Ulhaq; Imelda Safana Hidayat; Siti Nurul Iftitah (FKIP, Universitas Palangka Raya, 2025)
Stunting, as a result of chronic malnutrition, remains a serious issue in Girirejo Village, Tempuran District, Magelang Regency, with eight toddlers identified as experiencing this condition. To address this, a community service initiative was conducted involving mothers who are members of the Posyandu (Integrated Health Post), aiming to raise awareness about the importance of balanced nutrition and provide training in preparing nutritious meals. The methods employed included observation, counseling, training, and publication of activity outcomes. The research findings indicate an improvement in mothers' knowledge about stunting and its prevention, supported by Posyandu activities such as weight and height measurements of toddlers, as well as the provision of Supplementary Feeding (PMT) in the form of Dancow formula milk, as part of efforts to prevent stunting and improve toddlers' nutritional status. Training in preparing Supplementary Feeding, including demonstrations on making healthy dimsum and purple yam pudding by UNTIDAR KKN students, is expected to enhance nutritional awareness among the community of Girirejo Village. This study provides a significant contribution to more effective and sustainable stunting prevention efforts.